Ovarian Cancer Stem Cells with High ROR1 Expression Serve as a New Prophylactic Vaccine for Ovarian Cancer - Di Wu; Xiaoyu Yu; Jing Wang; Xu Hui; Yunxia Zhang; Yunlang Cai; Mulan Ren; Mei Guo; Fengshu Zhao; Jun Dou (Journal of Immunology Research)
Tumor vaccines offer a number of advantages for cancer treatment. In the study, the vaccination with cancer stem cells (CSCs) with high expression of the type I receptor tyrosine kinase-like orphan receptor (ROR1) was evaluated in a murine model for the vaccine’s immunogenicity and protective efficacy against epithelial ovarian carcinoma (EOC). CD117+CD44+ CSCs were isolated from human EOC HO8910 cell line using a magnetic-activated cell sorting system; murine ID8 EOC suspension sphere cells, which are collectively known as cancer stem-like cells, were acquired from serum-free suspension sphere-forming culture. Mice were subcutaneously immunized with the repeat cycles of freezing and thawing whole HO8910 CD117+CD44+ CSCs and ID8 cancer stem-like cells, respectively, followed by a challenge with HO8910 or ID8 cells at one week after final vaccination. The results showed that the CSC vaccination significantly induced immunity against EOC growth and markedly prolonged the survival of EOC-bearing mice in the prophylactic setting compared with non-CSC vaccination. Flow cytometry showed significantly increased immunocyte cytotoxicities and remarkably reduced CSC counts in the CSC-vaccinated mice. Moreover, the protective efficacy against EOC was decreased when the ROR1 expression was downregulated by shRNA in CSC vaccines. The findings from the study suggest that CSC vaccines with high ROR1 expression were highly effective in triggering immunity against EOC in vaccinated mice and may serve as an effective vaccine for EOC immunoprophylaxis.